Biological Barrier Models-on-Chips: A Novel Tool for Disease Research and Drug Discovery - Giusi Caragnano; Anna Grazia Monteduro; Silvia Rizzato; Gianluigi Giannelli; Giuseppe Maruccio (Biosensors, 2025)
The development of alternatives to animal models and traditional cell cultures has led to the emergence of organ-on-chip (OoC) systems, which replicate organ functions under both physiological and pathological conditions. These microfluidic platforms simulate key tissue interfaces—such as tissue–air, tissue–liquid, and tissue–tissue interactions—while incorporating biomechanical stimuli to closely resemble in vivo environments. This makes OoC systems particularly suitable for modeling biological barriers such as the skin, the placenta, and the blood–brain barrier, which play essential roles in maintaining homeostasis. This review explores various biological barrier models that can be replicated using the OoC technology, discussing the integration of induced pluripotent stem cells (iPSCs) to advance personalized medicine. Additionally, we examine the methods for assessing barrier formation, including real-time monitoring through integrated sensors, and discuss the advantages and challenges associated with these technologies. The potential of OoC systems in disease modeling, drug discovery, and personalized therapeutic strategies is also highlighted.